Hypervalent Iodine (III) Catalyzed Regio- and Diastereoselective Aminochlorination of Tailored Electron Deficient Olefins via GAP Chemistry - Rahman, Anis Ur; Zarshad, Nighat; Zhou, Peng; Yang, Weitao; Li, Guigen; Ali, Asad (Frontiers in Chemistry, 2020)
Herein, we report a protocol for highly efficient hypervalent iodine (III) mediated, group-assisted purification (GAP) method for the regioselectivities and stereoselective aminochlorination of electron-deficient olefins. A series of vicinal chloramines with multifunctionalities were acquired in moderate to excellent yields (45–94%), by merely mixing the GAP auxiliary-anchored substrates with dichloramine T and tosylamide as chlorine/nitrogen sources and iodobenzene diacetate as a catalyst. The vicinal chloramines were obtained without any column chromatographic purification and recrystallization simply by washing the reaction mixture with a minimum amount of common inexpensive solvents and thus avoiding wastage of silica, solvents, time, and labor. The GAP auxiliary is recyclable and reusable. This strategy is easy to handle, cost-effective, greener, sustainable, environmentally benign, and mostly suitable for the syntheses of vicinal haloamines from various electron-deficient alkenes.